STEPS OF CREATION AND STORAGE OF INFORMATION SECURITY SYSTEM (Conference Zone, 2022)
In practice, the creation of an information security system is carried out in three stages. In the first stage, the company is developing a basic model of the operating system. To do this, it is necessary to analyze all types of information that circulate in the company and should be protected from intrusion by third parties